The Dialeqticue of Simile in Bayhaqi's History - قدسیه رضوانیان; زهرا مقدسی (مطالعات زبانی و بلاغی)
Simile is a technic for expressing of history dynamically and with critic approach that Bayhaqi benefits of it. He uses from simile for expressing of his thoughts, to make dramatize imagine, to clear of issues, documentation and inspire to readers.